Relationship between ABO blood groups and mortality from SARS-CoV-2 infection in hospitalized patients - Oscanoa, Teodoro J. (2022)
This study aimed to determine the relationship between ABO blood groups and mortality in patients hospitalized for severe SARS-CoV-2 infection. An observational and retrospective research was conducted in a tertiary care hospital in Lima, Peru. A total of 203 patients with a mean age of 62.58 ± 16.45 years were included in the research, out of whom 71.92 % were males. The frequency of O, A and B blood groups were 75.37 %, 17.24 % and 7.39 %, respectively. An association with mortality from severe COVID-19 infection was found with non-A blood groups (O group or B group), with a PR (prevalence ratio) of 2.25 and 95% CI (confidence interval) of 1.07 – 4.71. When adjusting the main variables, the association with PR remained in 2.78 and 95% CI in 1.06 – 7.24. In conclusion, patients hospitalized for severe SARS-CoV-2 infection with O and B blood groups seem to be associated with higher mortality rates than those with A blood group.